Corporate And Functional Human Resources Development Strategy For Developing Countries - Begley, Thomas M. (Forum Manajemen; Vol 10 No 62 (1996): Forum Manajemen Prasetiya Mulya | Zaman Revolusi Gelombang Ketiga dan lmplikasinya, 1996)
Indonesia has shown impressive increases in Gross Domestic Product on an annual basis since the late 1960s. However, changed conditions in the world economy of the 1990s present increased challenges to any country that is seeking to continue its economic development.